Toddlers and Preschoolers Understand That Some Preferences Are More Subjective Than Others. Issue 3 (10th May 2021) - Doan, Tiffany; Friedman, Ori; Denison, Stephanie
Abstract : Four experiments examined Canadian 2‐ to 3‐year‐old children's ( N = 224; 104 girls, 120 boys) thoughts about shared preferences. Children saw sets of items, and identified theirs and another person's preferences. Children expected that food preferences would be more likely to be shared than color preferences, regardless of whether the items were similar or different in appeal (Experiments 1–3). A final study replicated these findings while also exploring children's expectations about activity and animal preferences. Across all studies, children expected shared preferences at surprisingly low rates (never higher than chance). Overall, these findings suggest that young children understand that some preferences are more subjective than others, and that these expectations are driven by beliefs about domains of preferences.